In vivo nerve identification in head and neck surgery using diffuse reflectance spectroscopy. Issue 5 (9th August 2018) - Langhout, Gerrit C.; Kuhlmann, Koert F.D.; Schreuder, Pim; Bydlon, Torre; Smeele, Ludi E.; van den Brekel, Michiel W.M.; Sterenborg, Henricus J.C.M.; Hendriks, Benno H.W.; Ruers, Theo J.M.
Abstract : Background: Careful identification of nerves during head and neck surgery is essential to prevent nerve damage. Currently, nerves are identified based on anatomy and appearance, optionally combined with electromyography (EMG). In challenging cases, nerve damage is reported in up to 50%. Recently, optical techniques, like diffuse reflectance spectroscopy (DRS) and fluorescence spectroscopy (FS) show potential to improve nerve identification. Methods: 212 intra‐operative DRS/FS measurements were performed. Small nerve branches (1–3 mm), on near‐nerve adipose tissue, muscle and subcutaneous fat were measured during 11 surgical procedures. Tissue identification was based on quantified concentrations of optical absorbers and scattering parameters. Results: Clinically comprehensive parameters showed significant differences (<0.05) between the tissues. Classification using k‐Nearest Neighbor resulted in 100% sensitivity and a specificity of 83% (accuracy 91%), for the identification of nerve against surrounding tissues. Conclusions: DRS/FS is a potentially useful intraoperative tool for identification of nerves from adjacent tissues. Level of Evidence: Observational proof of principle study.